2020
DOI: 10.21873/invivo.11841
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis of Pathological T3a Upstaging in Clinical T1 Renal Cell Carcinoma

Abstract: Aim: To evaluate the oncological outcomes of pathological T3a upstaging from clinical T1 renal cell carcinoma. Patients and Methods: We retrospectively studied patients who underwent radical or partial nephrectomy for clinical T1 renal tumors. Results: The median follow-up period was 44 months. At three and five years, the respective overall survival rate was 88. 7% and 82.4% in pT3a disease, 95.7% and 93.4% in pT1 (p=0.008), the cancer-specific survival rate, 93.9% and 90.8% in pT3a, 99% and 97.7% in pT1 (p=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, the analysis of fulltext articles was performed based on pre-established inclusion criteria. Finally, 12 studies [11][12][13][14][15][16][17][18][19][20][21][22] with a total of 7406 patients were included. Information on the included studies is shown in Table 1.…”
Section: Systematic Review Process and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the analysis of fulltext articles was performed based on pre-established inclusion criteria. Finally, 12 studies [11][12][13][14][15][16][17][18][19][20][21][22] with a total of 7406 patients were included. Information on the included studies is shown in Table 1.…”
Section: Systematic Review Process and Quality Assessmentmentioning
confidence: 99%
“…Among them, three studies used propensity score matching. 11,15,18 There were five studies performed in the USA, 11,15,[19][20][21] three in Korea, 12,14,17 two in China, 13,18 and one each in Canada 16 and Germany. 22 All of the trials enrolled patients diagnosed with upstage pT3 RCCa from cT1 renal tumor, who had undergone either PNx or RNx.…”
Section: Systematic Review Process and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation